Insights on the Efficacy and Safety of Selected Herbal Teas (Sciences of Phytochemistry, 2023)
Herbal teas are very common around the world. It has a good therapeutic effect. But due to adulteration, we face an obstacle to using them. The author has collected some clinical trials on commercial herbal tea formulations on the market that have proven their efficacy and safety. So, the future is for herbal medicine owing to people's psychology, minimum adverse reactions, and lower cost. The pharmaceutical manufacturing of herbal tea formulations should be encouraged to use them as add-on therapy or healthy daily beverages at least.